Making models to simulate testicular swellings. (2nd February 2017) - Sarmah, Piyush B; Sarmah, Bhupendra D; Ibrahim, Husam; Panting, Jonathan
Summary: Background: Testicular examination and the recognition of common scrotal swellings is a key clinical skill that is difficult to teach undergraduates because of its intimate nature. A novel approach for this topic was prompted by the description of handmade models in the medical literature to teach anatomical knowledge and clinical skills. Methods: Affordable low‐cost materials were purchased and assembled to form six models replicating key scrotal pathologies: epididymal cyst, epididymitis, hydrocoele, inguinoscrotal hernia, testicular tumour and varicocoele. They were used to teach the examination of testicular swellings to undergraduate medical students alongside a rubber manikin exhibiting testicular tumours, and all participants were invited to complete a post‐session evaluation on their experiences. Results: There were 66 participants in total: 83.3 per cent felt that the handmade models were more beneficial and 81.8 per cent would recommend them to colleagues to train in testicular examination, rather than the rubber model. The most common reasons provided were the greater variety of pathologies demonstrated, separate models for each pathology and the presence of key diagnostic features for certain swellings. The recognition of common scrotal swellings is a key clinical skill that is difficult to teach undergraduates Discussion: These models took approximately 1 hour to assemble. We hope that they can be widely used by Urology departments as a cost‐effective aid in the practical teaching of testicular examination and recognition of common scrotal swellings, thus reducing the dependency and intimacy of examining real patients with clinical signs.